2012
DOI: 10.1159/000343895
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Characterization of Retinoic Acid-Inducible Gene-I-Like Receptors of Mast Cells in Response to Viral Infection

Abstract: To investigate the precise mechanisms of virus recognition by mast cells, the expression and functional characteristics of virus recognition receptors that lead to mast cell activation were investigated. Our results suggest that mast cells are partly responsible for the early in vivo production of antiviral cytokines and chemokines upon vesicular stomatitis virus (VSV) infection. Analysis of the expression of double-stranded RNA (dsRNA) recognition receptors in murine bone marrow-derived mast cells (BMMCs) rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…In contrast, the expression of TNF‐α and IL‐6 was decreased significantly on days 3 and 5 pi in SCG‐treated mice, which suggests that SCG could improve the mortality of virus‐infected mice by preventing the overproduction of proinflammatory cytokines. Many studies have found that mast cells could be involved in virus infection using TLR3, RIG‐I, and MDA5 to sense viral RNA 43, 44, 45. In our study, the expression of TLR3 and TRIF in the lungs of SCG‐treated mice decreased, which suggested that SCG might have some roles in the TLR3 pathway in mast cells during H5N1 infection.…”
Section: Discussionsupporting
confidence: 49%
“…In contrast, the expression of TNF‐α and IL‐6 was decreased significantly on days 3 and 5 pi in SCG‐treated mice, which suggests that SCG could improve the mortality of virus‐infected mice by preventing the overproduction of proinflammatory cytokines. Many studies have found that mast cells could be involved in virus infection using TLR3, RIG‐I, and MDA5 to sense viral RNA 43, 44, 45. In our study, the expression of TLR3 and TRIF in the lungs of SCG‐treated mice decreased, which suggested that SCG might have some roles in the TLR3 pathway in mast cells during H5N1 infection.…”
Section: Discussionsupporting
confidence: 49%
“…Similar to our results with IAV, chemokine expression by mast cells in response to dengue virus infection was dependent on sensing by both the cytosolic RNA sensors, RIG-I and Mda5 (19, 20). Moreover, IL-6, CXCL10, and type I interferon expression by BMCMC in response to VSV treatment was dependent on RIG-I and Mda5 (60). Upon interacting with RNA, RIG-I and Mda5 undergo a conformational change allowing it bind with the scaffolding protein MAVS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, histamine production by BMCMC after IAV infection was normal in the absence of RIG-I. Analogously, BMCMC degranulation in response to VSV treatment occurred normally following RIG-I or Mda5 knock-down by siRNA (60). Other pattern-recognition receptors detecting early stages of the IAV infectious cycle could be important, such as TLR3 or TLR7 (3436).…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded viral RNA is sensed by TLR7 and TLR8, whereas viral DNA is detected by TLR9 [43]. MCs also express RIG-I protein kinase RNA-activated (PKR), and melanoma differentiation-associated gene 5 (MDA5), which recognize viral and synthetic dsRNA and induce MC activation and antiviral cytokine and chemokine production without degranulation [35, 36]. Human β-defensin-3 and 4 can also contribute to MC degranulation, prostaglandin D 2 generation, and chemotaxis [44].…”
Section: Mast Cell Activationmentioning
confidence: 99%